2019
DOI: 10.1007/s40272-019-00344-8
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in the Management of Children with Cerebral Palsy

Abstract: During the past 25 years, botulinum toxin type A (BoNT-A) has become the most widely used medical intervention in children with cerebral palsy. In this review we consider the gaps in our knowledge in the use of BoNT-A and reasons why muscle morphology and function in children with cerebral palsy are impaired. We review limitations in our knowledge regarding the mechanisms underlying the development of contractures and the difficulty in preventing them. It is clear from this review that injection of BoNT-A in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(193 citation statements)
references
References 132 publications
(385 reference statements)
4
155
1
14
Order By: Relevance
“…Therefore, we found little evidence that the reduction in hyperactive stretch reflex of the MG post BoNT-A induced muscle remodeling. It is known that the muscle needs more time than the current shortterm (two weeks) follow-up to adapt and no conclusions can be drawn about the medium-and long-term effect of BoNT-A on muscle length (43). Furthermore, muscle remodeling might take place after combining with casting.…”
Section: Bont-amentioning
confidence: 99%
“…Therefore, we found little evidence that the reduction in hyperactive stretch reflex of the MG post BoNT-A induced muscle remodeling. It is known that the muscle needs more time than the current shortterm (two weeks) follow-up to adapt and no conclusions can be drawn about the medium-and long-term effect of BoNT-A on muscle length (43). Furthermore, muscle remodeling might take place after combining with casting.…”
Section: Bont-amentioning
confidence: 99%
“…Muscle force-generating capacity is influenced by muscle cross-sectional area [3,4,10,11,17]. Muscle cross-sectional area is highly correlated with muscle thickness, and muscle thickness measured using ultrasonography can be used as a surrogate marker of change in muscle strength [3].…”
Section: Changes In Medial Head Of the Gastrocnemius Muscle Thicknessmentioning
confidence: 99%
“…Recently, Multani et al reported that human volunteers and experimental animals showed muscle atrophy after injections of BoNT-A for at least 12 months [17]. It is unclear whether these changes, mediated at the molecular level, are reversible; muscle atrophy was accompanied with the loss of muscle contraction and replacement by fat and connective tissue [17].…”
Section: Changes In Medial Head Of the Gastrocnemius Muscle Thicknessmentioning
confidence: 99%
See 2 more Smart Citations